The trial - Kafka, Franz, 1883-1924.; Wyllie, David (Mineola, N.Y. : Dover, 2009)
Josef K. is suddenly arrested and must spend the rest of his life fighting a charge against him about which he can get no information.
Originally published: Verlag die Schmiede : 1925.
Translation of: Prozess.
Adult
Keywords: Trials -- Fiction; Allegories; Trials -- Fiction; Allegories